Depression of bone marrow colony formation in gold-induced neutropenia. Issue 5955 (22nd February 1975) - Howell, A; Gumpel, J M; Watts, R W
Abstract : Bone marrow culture in semi-solid agar was used to assess the proliferative activity and the response to sodium aurothiomalate of the myeloid precursor cells from patients during and after recovery from neutropenia associated with the use of this drug. Colony formation was reduced during the neutropenia and returned to normal after recovery. The rheumatoid process itself did not impair colony formation even in patients with Felty's syndrome. Sodium aurothiomalate inhibited colony formation by normal marrow in a dose-dependent manner. Bone marrow colonies from patients who had recovered from neutropenia induced by sodium aurothiomalate were not abnormally sensitive to the inhibitory effect of the drug in vitro. The metabolism of gold is probably altered in a small proportion of patients, which causes high local concentrations within the bone marrow leading directly to marrow depression.